Imaginário poético de Leonilda Hilgenberg Justus e Olga Grechinski Zeni: amor e religiosidade - Kroin, Vanderlei (2022)
This work aims to investigate the poetic imaginary operating in the conjuncture of the works of the authors Leonilda Hilgenberg Justus and Olga Grechinski Zeni, from Paraná, analyzing the lyrical images of love and the divine/religious built throughout the verses. It was also an objective to observe how these images intertwine and talk with one another, relating to the mythical and in a communion with images of nature. In order to do that, this study is based on the theory of the imaginary of Gilbert Durand (1995; 1996; 2002; 2014) and the phenomenology of Gaston Bachelard (1989; 1993; 1994; 2001; 2003; 2009; 2013; 2018) and it is also anchored on poetic theories, focused on writers such as Octavio Paz (1972; 1979; 1993; 1994), Alfredo Bosi (2000), Mikel Dufrenne (1969), Ana Maria Lisboa de Melo (2002), Maria Zaira Turchi (2003), among others. The poetic investigation also has a strong dialogue with other areas, such as Plato’s philosophy (1999; 2005) and Aristotle (2013) and theoretical considerations on love and religion, found in authors such as Clive Staples Lewis (2017) and Denis de Rougemont (1988). In a similar way, since this is a literary study (poetry), characterized by its multiple meanings and as a cultural and symbolic heritage of humanity, we traced approaches of the poetic with other areas such as the psychoanalysis of Carl Gustav Jung (1982; 1987; 2005; 2008; 2011) and the history of myths and religions of Mircea Eliade (1972; 1991; 1998; 2018). Simultaneously, since the work of literature is a means of knowledge and cultural expression, the objective is to portray these two poetic voices as active subjects whose names deserve to be highlighted in the literary scenario of Parana, since they also contributed with the growth of literature in the state.